Activation of Chymotrypsinogen by Preparations of Thrombokinase Derived from Bovine Plasma - Milstone, J. H; Milstone, V. K (Thrombosis and Haemostasis, 1967)
Activation of chymotrypsinogen by thrombokinase was observed by the use of benzoyl tyrosine ethylester, which was hydrolyzed by chymotrypsin but not by thrombokinase. Optimal pH was 7.5 to 7.7; and 0.0035 M calcium chloride was beneficial. The ratio of chymotrypsinogen to thrombokinase could reach 1,000, without evidence that the zymogen was saturating the activator. But it was convenient to use a ratio near 20, with 2 mg chymotrypsinogen/ml. The early rate of activation was proportional to the concentration of thrombokinase; and this was made the basis for an assay of activator.The thrombokinase was a highly purified derivative of bovine plasma; but it was a weak chymotrypsinogen activator compared to trypsin. Nevertheless, activation could proceed in the presence of pancreatic trypsin inhibitor, in which case added trypsinogen caused no acceleration. Apparently, the activating effect was exerted directly on chymotrypsinogen. The ratio of activator to thrombin increased 2,000 fold during purification. Hence, activation was not due to the remaining trace of thrombin; although it could be due to some other impurity. However, it is possible that a single enzyme, namely thrombokinase, is able to split toluenesulfonylarginine methylester and also to activate prothrombin and chymotrypsinogen, respectively.